2015
DOI: 10.1063/1.4921806
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of anisotropic two-dimensional materials monolayer HfS2 and phosphorene metal-oxide semiconductor field effect transistors

Abstract: Ballistic transport characteristics of metal-oxide semiconductor field effect transistors (MOSFETs) based on anisotropic two-dimensional (2-D) materials monolayer HfS2 and phosphorene are explored through quantum transport simulations. We focus on the effects of the channel crystal orientation and the channel length scaling on device performances. Especially, the role of degenerate conduction band (CB) valleys in monolayer HfS2 is comprehensively analyzed.Benchmarking monolayer HfS2 with phosphorene MOSFETs, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Theoretically, the heterostructures of transition metal chalcogenides have been predicted to be strong absorbers of light and are suitable materials for photocatalysis application [13]. Field effect transistor based on monolayer HfS 2 has been reported [14]. Recent studies have shown that the band gap of TMCs can be engineered by building TMCs heterostructures [15][16][17] or thinning them down to monolayer [18][19][20][21].…”
mentioning
confidence: 99%
“…Theoretically, the heterostructures of transition metal chalcogenides have been predicted to be strong absorbers of light and are suitable materials for photocatalysis application [13]. Field effect transistor based on monolayer HfS 2 has been reported [14]. Recent studies have shown that the band gap of TMCs can be engineered by building TMCs heterostructures [15][16][17] or thinning them down to monolayer [18][19][20][21].…”
mentioning
confidence: 99%
“…[31][32][33] Low dimensional materials are interesting not only because they can provide access to novel physical phenomena, but also because their unique electrical, optical and mechanical properties make them the focus of attention. [34][35][36][37][38] MoS 2 crystal is composed of Mo atomic layer sandwiched between two layers of S, forming a triangular prismatic arrangement. 39,40 The Mo-S bonding is strong covalent, but the coupling between MoS 2 monolayer is weak van der Waals interactions.…”
mentioning
confidence: 99%
“…For arsenene, however, we suppose a negligible effect of the transport direction owing to the degenerate CB valleys located between Γ and M points in the hexagonal 1 st BZ. As discussed in the anisotropic 2-D material HfS 2 MOSFETs 35 , aligning one valley in the light effective mass direction is always accompanied by the alignment of the other valleys in the heavy effective mass direction. Therefore, current increase or decrease in one valley is compensated by current decrease or increase in the other valleys, which results in little change in total current.…”
Section: Resultsmentioning
confidence: 93%
“…For the performance assessment against the other 2-D material MOSFETs, we also simulate monolayer phosphorene homostructure MOSFETs with the doping levels of 5 × 10 13 and 1 × 10 14 /cm 2 . We choose phosphorene since phosphorene has been identified as one of the best candidates for 2-D material MOSFETs among the various 2-D materials due to the highly anisotropic CB and VB valleys 35,37 as in Fig. S2.…”
Section: Resultsmentioning
confidence: 99%